Application of the Chaining Method to Improve Toilet Training Skills in Children Aged 1-3 Years - Khairunnisa, Mutiara (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Toilet training is learning or an effort to train children so they can understand how to control themselves to feel when they want to urinate and train children's independence to carry out the toileting process independently. Where toilet training itself is carried out to teach children to be able to control urination and defecation. Children are generally able to carry out toilet training from the age of 18 months or 1.5 years to 2 years. However, in reality, not all children aged 1-3 years are capable of toilet training. One way to improve toilet training is by chaining technique. The aim of this research is to determine the effectiveness of using the chaining method in improving toilet training abilities in children. The type of research used is action research which consists of four elements including planning, action, observation and evaluation of the topics studied using observation and interview research methods which go through three stages of research time, namely intake, baseline and treatment. The place where this research was conducted was the subject's aunt's house because that was the most likely place for this behavior modification intervention to be carried out. The subject's aunt's house also has adequate toilet facilities for this intervention to be carried out. The results of the research showed that using the chaining method can improve toilet training abilities in children aged 1-3 years.